COSO enterprise risk management: small-medium enterprises evidence / Angeline Kiew Heong Yap and Saw Teng Yap - Kiew Heong Yap, Angeline; Yap, Saw Teng (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
The implementation of Enterprise Risk Management (ERM) is vital for all types of organisation including the small and medium enterprises (SMEs). Thus, the objective of this study was to examine perception of the ERM framework among SMEs in Malaysia, and to analyse its effect on sales performance. ERM is becoming an issue of high concern among organisations. This is because it is hailed as one of the most important framework to provide a clear direction and guidance in managing the risks of enterprises, so that the organisation is able to minimise risk and losses. In this study, a survey of one hundred and fifty-two (152) SMEs was conducted and the data was analysed using regression analysis. This study found that SMEs focus heavily on the “control environment” and “risk appetite” components. These two (2) components were ranked as the top ERM framework by SMEs in Malaysia. The Regression result suggests that “assessing risk management”, “control activities”, “information and communication” and “monitoring” components proved to have a significant effect on sales. This paper further contributes to knowledge development on ERM framework and the influences of its components on sales performance from a dynamic capability perspective of SMEs. SMEs should primarilyconsider the influence of dynamic capabilities and changing resources in their organisations when practising ERM for its survival.